Interior printing features - Chepurna, К.; Terpilovska, Y. (ТОВ «Друкарня Мадрид», 2024)
There is a constant demand in the printing services market for large-format printed products for interior decoration and outdoor advertising. Given the growing demands on the quality and uniqueness of visual solutions in interiors, the need to use new technologies is becoming more urgent. Innovative digital printing technologies are being introduced to create unique and inimitable interiors and to decorate points of sale. Production of large-format products for interior decoration of apartments, offices, exhibitions, concerts, shopping centres, restaurants, cafes and other establishments is called interior printing.
Keywords: printing